Practical Activities Promoting Engagement in Forest Ecology Research - Pieristè, Marta; Hartikainen, Saara M.; Jones, Alan G.; Kotilainen, Titta K.; Peltonen, Aino; Loehr, John; Robson, Thomas Matthew (Ubiquity Press, Ltd., 2022)
Improving public engagement in ecological research improves the visibility of science and educates a wider audience about the value of ecology and its study. To this end, we assess the success of two simple activities, designed to track forest cover and understorey conditions, implemented at Lammi Biological Station Science Trail, Finland, in terms of effective public participation and useability of the data generated. We consider how best to engage participants in the activities, and we validate the data obtained by comparison of its reliability and useability against standard ecological approaches. It is also increasingly timely for researchers to utilise the large datasets that can be generated through effective public engagement. If experiments are effectively designed, these data can provide information at a larger scale than is attainable with the resources typically available to individual research projects. Consequently, given high enough uptake, such activities hold the potential for upscaling or generalisation from their findings. Both activities proved useful to collect more intensive data than would otherwise have been feasible. The quadrat vegetation survey (Activity 1) provided useable data to determine species phenology but not species composition. The canopy disk observations (Activity 2) reliably tracked seasonal changes in canopy cover when calibrated against baseline data. Training in these activities fostered engagement in how climate change affects forest ecology, improving the quality of data collected, and engaging participants eager to learn about and contribute to research into these processes.
Keywords: Science education; public outreach; Research Nature Trail; canopy ecology; phenology; photobiology